Value-addition for jute and allied fibres - Sinha, M K; Ramasubramanian, T; Kundu, A (Indian Farming, 2015)
The CRIJAF has developed product-specific varieties for value addition. Antioxidant potentiality of ‘S 19’ leaves is higher than that of carrot and hence, this variety may be exploited for vegetable purpose. ‘MT 150’ was identified as the best paper pulp variety. ‘JBO 2003-H’ (‘Ira’) and ‘RRPS-27-C-3’ (‘Monalisa’) may be considered for textile purpose, while ‘JRO 524’ may be given priority for geo-jute. Sisal wax, jute leaf manure, sisal based insecticides, may pay the way for betterment of jute and allied fibres.